On the anomalous optical conductivity dispersion of electrically conducting polymers: ultra-wide spectral range ellipsometry combined with a Drude–Lorentz model. Issue 15 (3rd April 2019) - Chen, Shangzhi; Kühne, Philipp; Stanishev, Vallery; Knight, Sean; Brooke, Robert; Petsagkourakis, Ioannis; Crispin, Xavier; Schubert, Mathias; Darakchieva, Vanya; Jonsson, Magnus P.
Abstract : Ultra-wide range spectral range ellipsometry sheds light on the anomalous optical conductivity of conducting polymers. Abstract : Electrically conducting polymers (ECPs) are becoming increasingly important in areas such as optoelectronics, biomedical devices, and energy systems. Still, their detailed charge transport properties produce an anomalous optical conductivity dispersion that is not yet fully understood in terms of physical model equations for the broad range optical response. Several modifications to the classical Drude model have been proposed to account for a strong non-Drude behavior from terahertz (THz) to infrared (IR) ranges, typically by implementing negative amplitude oscillator functions to the model dielectric function that effectively reduce the conductivity in those ranges. Here we present an alternative description that modifies the Drude model via addition of positive-amplitude Lorentz oscillator functions. We evaluate this so-called Drude–Lorentz (DL) model based on the first ultra-wide spectral range ellipsometry study of ECPs, spanning over four orders of magnitude: from 0.41 meV in the THz range to 5.90 eV in the ultraviolet range, using thin films of poly(3, 4-ethylenedioxythiophene):tosylate (PEDOT:Tos) as a model system. The model could accurately fit the experimental data in the whole ultrawide spectral range and provide the complex anisotropic optical conductivity of the material. Examining the resonance frequencies and widths of the Lorentz oscillators reveals that both spectrally narrow vibrational resonances and broader resonances due to localization processes contribute significantly to the deviation from the Drude optical conductivity dispersion. As verified by independent electrical measurements, the DL model accurately determines the electrical properties of the thin film, including DC conductivity, charge density, and (anisotropic) mobility. The ellipsometric method combined with the DL model may thereby become an effective and reliable tool in determining both optical and electrical properties of ECPs, indicating its future potential as a contact-free alternative to traditional electrical characterization.